Interfacial thermal conductance enhancement of BN/PVA composites via plasma activations of fillers. (December 2021) - Xu, Chenyang; Li, Erchun; Zeng, Jinjue; Wang, Yue; Wang, Tao; Ge, Cong; Zhang, Chen; Wang, Qi; Gao, Tian; Yao, Yagang; Jiang, Xiangfen; Zhang, Ya; et al.
Abstract: Polymeric composite materials for heat management play a key role in electronic packaging, yet they usually suffer from the interfacial thermal resistance when using ceramic fillers. The interfacial incompatibility and debonding between fillers and matrices are identified as the culprit. Boron nitride (BN) is an advanced thermal conductive filler, whereas it also suffers from the interfacial problem owing to its chemical inertia and hydrophobicity. Herein, some plasma activations are introduced to well functionalize BN, which significantly changes BN from hydrophobicity to hydrophilicity. The interfacial bonding is thus achieved between the plasma-treated BN fillers and the polyvinyl alcohol molecules. The BN/polyvinyl alcohol composite material shows a high through-plane thermal conductivity of 2.4 W m −1  K −1 for a filling fraction of 50 wt% BN treated by N2 plasma, which is much better than the raw BN case. It is thus envisaged as a promising approach for the high-efficiency and low-cost fabrication of BN-based composite materials. Graphical abstract: Image 1 Highlights: A high-efficiency and low-cost approach is developed for the surface modification of BN fillers via plasma activations. The plasma-treated BN contributes good interfacial bonding between BN fillers and polyvinyl alcohol molecules in their composite materials. The BN/PVA composite demonstrates high thermal conductivity  via  experimental tests as well as finite element simulations.